Assessment and Improvement of Daylighting Quality in Classrooms with Double-Side Windows - Ezzaddeen Ali Mohammed Saeed AL-Mowallad; Xianfeng Huang; Zhen Lu; Xiaofan Li; Kaiwen Wu; Zhirui Zhu; Guohuan Liu (Buildings)
Daylighting in educational buildings is a key factor in ensuring visual comfort and maintaining indoor environmental quality. In this context, daylight quality plays a crucial role in enhancing the lighting conditions within classrooms. Due to the local climate, classrooms with double-side windows are widely prevalent in southern China; however, these wide windows can sometimes lead to uncomfortable glare and uneven daylight distribution. In response, and to address and improve daylight quality, this study selected some classrooms at Guangxi University as a typical case study. The investigation of indoor daylighting performance and visual comfort was conducted through field surveys (questionnaires), on-site measurements, and software simulations. A comprehensive analysis was conducted using lighting environment metrics, including Daylight Factor (DF), Illuminance Uniformity, Effective Illuminance, Daylight Glare Probability (DGP), and Useful Daylight Illuminance (UDI). The findings revealed that large window glass areas on both sides could lead to high DF values, pronounced glare, and low UDI within classrooms. Subsequently, by analyzing influencing factors such as the window-to-floor ratio, window type, the optical properties of classroom interior surfaces, and window shading devices, strategies for improving daylight quality in these classrooms were proposed. The results of this study provide guidance for future daylighting design in university classrooms in hot and humid regions. Moreover, it offers valuable benefits to a wide range of stakeholders, including researchers, practitioners, and policymakers, while providing crucial insights for improving national building standards in this region.